Participatory practices in natural and cultural heritage - Travaglia, Andrea A. (Ex Novo: Journal of Archaeology, 2019)
Heritage planning in Europe, through the Valletta and Florence Conventions, constitutes a framework for cooperation whereby the public is encouraged to take an active part - an ongoing cultural practice that includes society. Within this paper, I focus on participatory practice as a reflective process of problem-solving in heritage via individuals working together as a community of practice and crowd-based approaches. The recent development of the Environment and Planning Act (Omgevingswet) in the Netherlands, which will legally frame the way municipalities and citizens interact with their environment, is used as a case study to show context-dependent risks associated with the democratic dialogue in heritage planning. Participatory planning is impossible without democratic participation, and there is a risk that the Omgevingswet will merely pay lip service to participatory practice. I analyse engagement with technology and the new law that is not yet operational - with its influence on citizen participation yet to form - that could either have negative consequences or potentially enhance the participatory governance process in the Dutch heritage sector. In conclusion, the medium (Omgevingswet online platform) is the message (integration of sustainable Dutch landscapes in national and regional environmental visions) for online participatory practice in a networked information economy.